RETRACTED ARTICLE: PHD2 acts as an oncogene through activation of Ras/Raf/MEK/ERK and JAK1/STAT3 pathways in human hepatocellular carcinoma cells - Junqiang Guo; Zhi Lan (Artificial Cells, Nanomedicine, and Biotechnology)
We, the Editors and Publisher of the journal Artificial Cells, Nanomedicine, and Biotechnology, have retracted the following article:Junqiang Guo & Zhi Lan (2020) PHD2 acts as an oncogene through activation of Ras/Raf/MEK/ERK and JAK1/STAT3 pathways in human hepatocellular carcinoma cells. Artificial Cells, Nanomedicine, and Biotechnology, 48(1), 37–45, DOI: 10.1080/21691401.2019.1699806Since publication, concerns have been raised about the integrity of the data in the article. When approached for an explanation, the authors have been unable to verify their original data or answer our questions about research ethics and the informed consent process. We are therefore retracting this article and the corresponding author listed in this publication has been informed.We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions.The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as “Retracted”.